“Where everybody knows your name”: How regulars at farmers' markets differ from less-frequent shoppers - Stobbe, Tracy (Frontiers in Sustainable Food Systems, 2023)
A survey of consumers at three farmers’ markets (FMs) was done near Vancouver, British Columbia. The markets span urban and suburb locales, and the survey’s 234 respondents were asked questions about shopping behaviour, attitudes toward FMs, and demographic information. The focus of the analysis is on the differences between regulars and non-regulars to the market, where a regular is considered a shopper who shops weekly or bi-weekly. The results show that regulars spend more (46.36 vs. 33.19 for non-regulars), are much more likely to expect higher prices compared to grocery stores than non-regulars, and buy more products (4.15 vs. 3.1). Regulars also value attributes of FMs differently: they value variety, organic products, and being locally-grown more highly. Organic purchasing behaviour is also significantly different with regulars much more likely to say they “always” or “usually” buy organic products. These results have implications for market managers and scholars of consumer behaviour.